DEVELOPMENT OF MULTIPLICATION BOARD TEACHING AIDS FOR THE INTEREST IN CALCULATING MULTIPLICATION OF GRADE III ELEMENTARY SCHOOL STUDENTS - cheche, cheche (Prima: Jurnal Pendidikan Matematika, 2024)
This research was conducted because there are still many grade III students who have a low interest in counting in mathematics lessons, especially in multiplication material. The purpose of this study is that researchers want to help students increase interest in counting in mathematics multiplication material by developing learning media in the form of multiplication boards that can meet the needs of grade III students of SDN Baru 03. The method used in this study is Reseaech and Development (R&D) using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). Experts and grade III students filled out questionnaires used in data collection. The participants of this study were grade III students of SDN Baru 03 using a small group of 5 students getting a percentage of 94% and a large group of 30 students getting a percentage of 91%, both showing very decent categories. In addition, there are 2 media experts who get a percentage of 88% and 100% with a very decent category. For material experts, it gets a percentage of 92% with the category very worthy of use. It can be concluded that the multiplication board media  is very feasible to use, especially for grade III students of SDN Baru 03 in the Mathematics lesson of multiplication material.